Analisis Pengaruh Iklan Judi Slot Online pada Situs Tokyo99 terhadap Masyarakat Kabupaten Sumbawa - Alfian K, Sukma Deva Noer (YASIN, 2024)
The current development of the internet really helps people so that they can communicate easily without having to meet in person or communicate long distances. This is a positive impact for someone who uses internet technology media wisely. Those who initially used the Internet only to access learning information, games and social media, then because of the curiosity of young people, some began to access online gambling games. One of the online slot gambling sites is TOKYO99. The behavior of playing online slot gambling can have a negative impact on the perpetrator and the social environment. The impact that can arise from this gambling behavior is usually called the Phatalogical Gambler. The aim of this research is to determine the influence of advertising on the TOKYO99 site in promoting online slot gambling games to the people of Sumbawa Regency. This research uses a descriptive qualitative approach method. Qualitative research methods are qualitative data processing techniques carried out in order to describe or discuss research results using conceptual analysis and theoretical analysis approaches. This thesis also uses the theory of syringes and uses and gratification. The research results show that the TOKYO99 site uses social media as promotional material to encourage people to play online slot gambling. In playing online slot gambling games, the TOKYO99 site offers quite fantastic results, so that people who see this online slot gambling advertising promotion are interested and start playing the game.